Construction of hierarchical CoP@Ni2P core–shell nanoarrays for efficient electrocatalytic hydrogen evolution in alkaline solution. Issue 36 (24th June 2021) - Jin, Hao; Liu, Shuo; Pei, Lang; Li, Gao; Ma, Zhanfeng; Bai, Wangfeng; Wu, Shiting; Yuan, Yong-Jun; Zhong, Jiasong
Abstract : Benefiting from their structural and compositional merits, the as-synthesized CoP@Ni2 P core–shell nanoarrays exhibit excellent electrocatalytic activity and long-term stability for HER in 1 M KOH. Abstract : Design and synthesis of non-noble electrocatalyst with controlled structure and composition for hydrogen evolution reaction (HER) are significant for large-scale water electrolysis. Here, an elegant multi-step templating strategy is developed for the fabrication of vertically aligned CoP@Ni2 P nanowire–nanosheet architecture on Ni foam. Cobalt–carbonate hydroxides nanowires grown on Ni foam are first synthesized as the self-template. Afterward, a layer of amorphous Ni(OH)2 nanosheets is grown on the Co-based precursors through a chemical bath process, which is then transformed into the hierarchical CoP@Ni2 P nanoarrays by a co-phosphatization treatment. Owing to the synergistic effect of the compositions and the advantages of the hierarchical heterostructures, the resulting hybrid electrocatalyst with dense heterointerfaces is revealed as an excellent HER catalyst, with a low overpotential of 101 mV at the current density of 10 mA cm −2, a relatively small Tafel slope of 79 mV dec −1, and favorable long-term stability of at least 20 h in 1 M KOH.